Areca nut chewing and systemic inflammation: evidence of a common pathway for systemic diseases - Shafique Kashif; Mirza Saira; Vart Priya; Memon Abdul; Arain Moin; Tareen Muhammad; Haq Zia (BMC, 2012)
Abstract Background Areca nut, the seed of fruit of an oriental palm, known as Areca catechu, is commonly chewed in many countries. Diabetes, hypertension, cardiovascular diseases, oropharyngeal and oesophageal cancers have been associated with areca nut chewing and the mechanism by which areca nut chewing increases the risk of systemic diseases remains elusive. We hypothesize that systemic inflammation may be elevated among areca nut users, which is linked with many systemic diseases. Therefore, this present study was conducted to examine the systemic inflammation among areca nut chewers and healthy controls. Methods This was an observational cross sectional study carried out on areca nut chewers and healthy individuals in Karachi, Pakistan. Participants were selected from a region of the city by invitation request sent from door to door. Information was collected regarding the socio-demographic profile and the pattern of use, and a blood sample was obtained to measure the level of C-reactive protein (CRP). We carried out multiple logistic regressions to investigate the association between socio-demographic profile, areca nut chewing and CRP levels. Results We carried out final analysis on 1112 individuals of which 556 were areca nut chewers and 556 were the age, gender and area matched controls. Areca nut chewers had a significantly higher proportion of men (15.1%, n = 84) who had an elevated CRP (>10 mg/dl) as compared to controls (5.2%, n = 29). Multivariate analyses showed that areca nut chewers had significantly higher odds of an elevated CRP (OR = 3.23, 95% CI 2.08-5.02, p value <0.001) as compared to controls. Increase in amount of areca nut consumption had a significant dose-response relationship with systemic inflammation (p for trend <0.001). Further analysis revealed that areca nut chewers with tobacco additives were two times more likely to have an elevated CRP as compared to raw areca nut users. These associations remained unchanged after adjustments for age, BMI and years of full time education. Conclusions Areca nut chewing has a significant association with systemic inflammation. Further work is required to confirm that systemic inflammation is the main pathway by which areca nut use increases the risk of systemic diseases.